SIMPLE TECHNIQUES TO ACTIVATE SCHEMATA - Ahmad Hijaz; Asrun Lio; Kamaluddin Kamaluddin (Journal of Language Education and Educational Technology (JLEET), 2021)
Activating schemata to improve reading comprehension has been acknowledged and well accepted in academic world for decades, however many teachers are still recultant to spare time in this area. It’s believed that activating schemata requires heavy preparation and certain additional skills aside from their existing ones.This article offers four simple techniques that can help activating students’ schemata which in turn allow them perform better in reading comprehension tasks. In addition, the techniques can be performed with minimum equipments and less time consumption